PENERAPAN STRATEGI PEMBELAJARAN AKTIF RODA KEBERUNTUNGAN UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI MIA MAN 1 PEKANBARU - Irnov, Masithah; Erna, Maria; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to improve the learning achievement of student on the Chemical Equilibrium subject in class XI MIA MAN 1 Pekanbaru. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class XI IPA 1 as the experiment class and students of class XI IPA 3 as the control class randomly determined after the test of normality and homogeneity test. Experiment class is a class that is applied to active learning strategy of lucky wheel while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount > ttable is 2,35 > 1,66, means that the use of learning active strategy of lucky whell can improve the learning achievement of students on the subject Chemical Equilibrium in class XI MIA MAN 1 Pekanbaru. The improvement category of student learning achievement at experimental class trhough N-gain test was high category with a value of N-gain 0,77.Keywords: Learning Achievement, Active Learning Strategy of Lucky Wheel, Chemical Equilibrium